National culture and corporate debt maturity - Zheng, Xiaolan; El Ghoul, Sadok; Guedhami, Omrane; Kwok, Chuck C.Y. (Journal of Banking & Finance, 2012)
We investigate the influence of national culture on corporate debt maturity choice. Based on the framework of Williamson, we argue that culture located in social embeddedness level can shape contracting environments by serving as an informal constraint that affects human actors’ incentives and choices in market exchange. We therefore expect national culture to be related to debt maturity structure after controlling for legal, political, financial, and economic institutions. Using Hofstede’s four cultural dimensions (uncertainty avoidance, collectivism, power distance, and masculinity) as proxies for culture, and using a sample of 114,723 firm-years from 40 countries over the 1991–2006 period, we find robust evidence that firms located in countries with high uncertainty avoidance, high collectivism, high power distance, and high masculinity tend to use more short-term debt. We interpret our results as consistent with the view that national culture helps explain cross-country variations in the maturity structure of corporate debt.